2015
DOI: 10.1007/s11581-015-1573-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate structure and lithium environments in lithium phosphorus oxynitride amorphous thin films

Abstract: International audienceLithium ion-conducting glasses attract wide interest for electrochemical applications like efficient energy storage devices. This work presents a structural study on involved bonding units, based on X-ray photoelectron spectroscopy and infrared spectroscopy, of lithium phosphorus oxide and oxynitride amorphous thin films prepared by RF magnetron sputtering. A thorough consideration of the mid- and far-infrared spectral regions demonstrated structural changes at the phosphate units and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…For the final change at about 1190 cm –1 , there could potentially be different modes involved, as the shoulder in the amorphous Li 3 PO 4 film mostly disappears, but the film with the highest N:O content also has an increased intensity relative to the other Lipon films. Previous work suggests that absorption around 1190 cm –1 in the pure oxide is due to the stretching of pyro-phosphate PO 3 groups, which would imply the presence of O b . Although we cannot exclude this possibility, since O b is seldom found in our modeled Lipon structures and is completely absent in the amorphous Li 3 PO 4 structure generated via AIMD, we will not follow such assignment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For the final change at about 1190 cm –1 , there could potentially be different modes involved, as the shoulder in the amorphous Li 3 PO 4 film mostly disappears, but the film with the highest N:O content also has an increased intensity relative to the other Lipon films. Previous work suggests that absorption around 1190 cm –1 in the pure oxide is due to the stretching of pyro-phosphate PO 3 groups, which would imply the presence of O b . Although we cannot exclude this possibility, since O b is seldom found in our modeled Lipon structures and is completely absent in the amorphous Li 3 PO 4 structure generated via AIMD, we will not follow such assignment.…”
Section: Resultssupporting
confidence: 91%
“…For instance, Wang et al also observed XPS peaks in polycrystalline Li 2.88 PO 3.73 N 0.14 at binding energies 397.8 and 399.7 eV but assigned them differently based on the support of X-ray diffraction and chromatography data revealing the presence of nonbridging or apical N (N a ) along with a minor portion of N d due to some Li–P disorder. Infrared (IR) spectroscopy, Raman spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy of amorphous Lipon and related materials have also been collected, , but their interpretations have assumed the above-mentioned structural hypothesis proposed by Bates et al is correct; thus, the identification of N-related modes that might solve this discrepancy also remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Such nitridation‐induced clustering of modifier cations around the pyrophosphate Q 1 (P) units detected in the Raman might generate percolation channels and presumably act as weak regions in the structure . Modification of modifier cation environment should be accompanied by vibrational changes in Raman spectra in the low‐frequency part of the spectrum (<400 cm −1 ), yet no distinguishable changes are observed.…”
Section: Resultssupporting
confidence: 85%
“…The latter was done by setting the areas of all the intensity peaks in the range of interest equal to 1. The band assignment of the Raman spectra was based on previously reported data for germanophosphate and oxynitride phosphate glasses …”
Section: Methodsmentioning
confidence: 99%
“…In this context, as general rule, amorphous oxynitrides have much higher charge carrier mobility than a-Si [10][11][12]. At the same time, amorphous oxynitrides presents homogeneous uniformity and high structural stability even though simple binary oxides tend to crystallize [13,14]. Moreover, the indium zinc oxynitride (IZON) is an excellent semiconductor for band gap engineering applications due to an easy tunable band gap [15,16].…”
Section: Introductionmentioning
confidence: 99%